Fir branch as rare cause of aspiration pneumonia in adults - S. N. Kosarev; A. H. Pazilov; D. A. Ochkas; N. Yu. Kolesnik; T. V. Sorokina; E. B. Topolnitsky; T. S. Ageeva (Бюллетень сибирской медицины)
The article represents a clinical observation describing the case of mechanical obstruction in the respiratory passages with an unusual foreign body, a fir branch. The diagnostic problem lied in the fact that a patient did not notice the fact of aspiration, the respiratory symptoms were non-specific, and the foreign body was radiotransparent. A detailed case history allowed the detection and endoscopic confirmation of the aspiration of a foreign body, a fir branch, and the consideration of the community acquired pneumonia and secondary aspiration pneumonia that required specialized medical care by the thoracic surgery department.